Israiliyyat Prophet Sulaiman In Tafsir Bi Al-Ma'thur: A Study Of Tafsir Al-Tashil Li 'Ulum Al-Tanzil By Ibn Juzay Al-Kalbi - Attarwiyah, Nadiatul Maziyyah; Hasan, Hamka; Sujoko, Imam (Jurnal Ushuluddin, 2024)
This study aims to explore the existence of israiliyyat contained in Tafsir al-Tashil li 'Ulum al-Tanzil by examining the verses of the story of Prophet Sulaiman in the Quran. The source of israiliyyat is essential to study in order to avoid deviant understandings that can damage the order of the creed of Islam and emphasize the interpretations that eliminate the kema'shuman of the Prophets. This research uses a qualitative method with a literature study. Data were obtained through an interpretive method using the hermeneutic approach to understand the phenomenon of shifting meaning and semiotics to get the most optimal meaning. The results showed that the story of the Prophet Sulaiman was classified into five themes, with four themes considered as the category that provide information only, and one theme was considered as the category of israiliyyat, namely the interpretation in Surah Shad verse 34 by providing a rebuttal to the false story and cannot be used as a reference for interpretation. Ibn Juzay also quotes some israiliyyat stories without criticism and judgment as to whether to reject or accept their narration, which can be called tawaqquf. Nevertheless, Ibn Juzay's interpretation does not contradict the Qur'an and the Hadith, does not damage the order of Islamic religious principles, and does not eliminate the humanity of the Prophet Sulaiman